Detection of Bar Transgenic Sugarcane with a Rapid and Visual Loop-Mediated Isothermal Amplification Assay - Zhou, Dinggang; Wang, Chunfeng; Li, Zhu; Chen, Yun; Gao, Shiwu; Guo, Jinlong; Lu, Wenying; Su, Yachun; Xu, Liping; Que, Youxiong (Frontiers in Plant Science, 2016)
Genetic engineering offers an attractive alternative in sugarcane breeding for increasing cane and sugar yields as well as disease and insect resistance. Bar transgenic sugarcane employing the herbicide tolerance is a useful agronomical trait in weed control. In this study, a loop-mediated isothermal amplification (LAMP) assay for rapid detection of the bar gene in transgenic sugarcane has been developed and evaluated. A set of six primers was designed for LAMP-based amplification of the bar gene. The LAMP reaction conditions were optimized as follows: 5.25 mM of Mg2+, 6:1 ratio of inner vs outer primer, and 6.0 U of Bst DNA polymerase in a reaction volume of 25.0 μL. The detection limit of the recombinant plasmid 1Ac0229 was as low as 10 copies in the developed LAMP, which was ten-fold higher sensitive than that of conventional PCR. In 100 putative transgenic lines, the bar gene was detected in 100/100 cases (100%) by LAMP and 97/100 cases (97%) by conventional PCR, respectively. In conclusion, the developed LAMP assay is visual, rapid, sensitive, reliable and cost-effective for detection of the bar specific transgenic sugarcane.